Three-dimensional morphometric analysis and development of new classification system of impacted canines in orthodontic patients using cone beam computed tomography - Alfarra, Yahya H.Y. (2022)
Canine teeth are aesthetically most dominant teeth which can present a smile as either holy or evil. They define the mouth’s corner, are involved in the aesthetic smile, maintain occlusal stability, and design the shape of the dental arch. As the position of the impacted canines is amidst vital anatomical structures like the nasal cavity and sinuses in the maxilla and mental nerve in the mandible, a thorough radiographic evaluation to determine the position of the impacted canines is of utmost importance prior to any treatment planning. By using a CBCT image, a clinician can clearly identify its location. The present study aimed to determine the prevalence of impacted canines in orthodontic patients and conduct morphometric analysis on the effect of impacted canines on the dental arch form and dimension and develop a new classification system. CBCT images of patients aged 15 to 50 years who attended HUSM, Malaysia, for orthodontic treatment were analysed pertaining to their arch and categorised under the proposed 3D classification system based on their location and direction during the state of impaction. The results suggested that the prevalence of impacted canines in orthodontic patients was 17.5 %, with a female preponderance. Impacted canines occurred most frequently in Class I malocclusion subjects and least in Class III malocclusion. A significant relationship between the impacted canines and adjacent anatomical structures was found in most measured variables. The impacted canines appeared to be interrelated with arch dimension measurements. The findings showed significant changes in the study group compared to the control group. Interpremolar, intermolar widths and arch length were significantly deficient and narrower, with higher palatal vault seen in impacted canine patients as compared to the control group. Based on the new classification system, the most common type of impacted maxillary canines was V1AP, followed by V2BP, V2AP, and V2CP. V3BL, N2AP and N3AP were the least common. For impacted mandibular canines, M1AP was predominant, followed by M2AP, M1CP, and M2AL. Whilst M1AL and M1BP were the least prevalent. The present 3D investigation provides a new clinical reference value for the prevalence of impacted canines based on ethnicity, gender, and different types of malocclusion in addition to the relationship with surrounding anatomical structures and dental arch dimensions. Furthermore, this study established a new system for classifying impacted maxillary and mandibular canines to facilitate interdisciplinary communication for better treatment planning.